2015
DOI: 10.1038/eye.2015.108
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of phacoemulsification on trabeculectomy function

Abstract: Purpose To investigate the long-term effect of phacoemulsification on intraocular pressure (IOP) in trabeculectomized eyes and to identify the factors affecting the IOP changes. Methods In consecutive patients with previous trabeculectomy (TE) who underwent uncomplicated clear cornea phacoemulsification we evaluated intraocular pressure, need of antiglaucomatous medical therapy or glaucoma surgery, and length of glaucoma control without therapy. Glaucoma therapy was prescribed in the presence of IOP 418 mm Hg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 22 publications
(33 reference statements)
3
24
0
2
Order By: Relevance
“…[448][449][450] Potential benefits of a combined procedure (cataract extraction with IOL implantation and trabeculectomy) are protection against the IOP rise that may complicate cataract surgery alone, the possibility of achieving long-term glaucoma control with a single operation, and elimination of the risk of bleb failure with subsequent cataract surgery when glaucoma surgery is performed first. [451][452][453] Therefore, an ophthalmologist may reasonably choose to perform a combined surgery because of these perceived advantages to an individual patient.…”
Section: Combined Surgeriesmentioning
confidence: 99%
“…[448][449][450] Potential benefits of a combined procedure (cataract extraction with IOL implantation and trabeculectomy) are protection against the IOP rise that may complicate cataract surgery alone, the possibility of achieving long-term glaucoma control with a single operation, and elimination of the risk of bleb failure with subsequent cataract surgery when glaucoma surgery is performed first. [451][452][453] Therefore, an ophthalmologist may reasonably choose to perform a combined surgery because of these perceived advantages to an individual patient.…”
Section: Combined Surgeriesmentioning
confidence: 99%
“…In comparison, only 5% patients in our group required cataract surgery in the study period. Cataract surgery can decrease the success of a trabeculectomy with an increased likelihood of post-operative interventions and requirement for glaucoma medication in 30–39% cases [ 20 , 21 ]. These risks are avoided with VC due to its bleb-independent mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Mierzejewski et al demonstrated the highest reduction of postoperative IOP which is 4 mmHg after phacoemulsification in eyes with POAG, however pseudoexfoliative glaucoma was included, and because no specific gonioscopic grading was shown, eyes with narrow angle before phacoemulsification can clarify the substantial reduction in postoperative IOP after surgery [25]. Other studies included eyes with normal tension glaucoma (NTG) or medically uncontrolled POAG [26,27]. These methodological variations possibly account for the high variability in the outcomes.…”
Section: Plos Onementioning
confidence: 99%